Technology and Responsibility
IX, 393 p.
Keywords: Since it may seem strange for a new series to begin with volume 3, a word of explanation is in order. The series, Philosophy and Technology, inaugurated in this form with this volume, is the official publication of the Society for Philosophy & Technology. Approximately one volume each year is tobe published, alternating between proceedings volumes - taken from contributions to biennial international conferences of the Society - and miscellaneous volumes, with roughly the character of a professional society journal. The forerunners of the series in its present form were two proceedings volumes: Philosophy and Technology (1983), edited by Paul T. Durbin and Friedrich Rapp, and Philosophy and Technology //: Information Technology and Computers in Theory and Practice (1986), edited by Carl Mitcham and Alois Huning - both published (as volumes 80 and 90, respectively) in the series, Boston Studies in the Philosophy of Science. The Society for Philosophy & Technology, now more than ten years old, is devoted to the promotion of philosophical schalarship that deals in one way or another with technology and technological society. "Philosophical scholarship" is interpreted broadly as including contribu tions from any and all perspectives; the one requirement is that the schalarship be sound, and all contributions to the series are subject to rigorous blind refereeing. "Technology," the other half of the philos ophy-and-technology pairing, is also construed broadly.